A study investigating the multifaceted toxicity induced by triflumuron insecticide in Allium cepa L - Gizem Bıyıksız; Tuğçe Kalefetoğlu Macar; Kültiğin Çavuşoğlu; Emine Yalçın (Scientific Reports)
Abstract As the use of insect growth regulators such as triflumuron becomes more prevalent in modern agriculture, concerns have emerged regarding their multifaceted toxicity in non-target species. In this study, the multifaceted toxicity of triflumuron insecticide in the non-target bioindicator organism Allium cepa L. was investigated. For this purpose, the physiological effects of triflumuron on A. cepa bulbs (germination percentage, weight gain, and root elongation) were screened. In addition, cytogenetic (chromosomal abnormalities = CAs, micronucleus = MN, mitotic index = MI, and DNA damage = Comet analysis) and biochemical (superoxide dismutase = SOD and catalase = CAT enzyme activities, malondialdehyde = MDA and proline accumulation, and chlorophyll a and chlorophyll b amounts) analyses were performed in A. cepa root tip cells exposed to triflumuron. Root tip meristematic cell damage was also among the parameters examined. Onion bulbs were divided into 4 groups. The control group was treated with tap water. The other 3 groups were treated with 1.6 µg/L triflumuron, 10.0 µg/L triflumuron and 24.2 µg/L triflumuron, respectively. The selected triflumuron doses were based on LC₅₀ values reported for aquatic and terrestrial organisms to reflect environmentally relevant exposure levels. The application period lasted 72 h for root development and 144 h for leaf growth required for chlorophyll analysis. Triflumuron insecticide significantly reduced germination, root elongation, and weight gain in all groups. The decline in the values of physiological parameters was exacerbated with increasing dose of triflumuron. Triflumuron administration increased the frequency of MN and CAs, and decreased MI. CAs induced in the triflumuron-exposed groups were ranked according to their frequency as sticky chromosome, fragment, vagrant chromosome, unequal distribution of chromatin and bridge. Comet assay showed a considerable increase in the percentage of tail DNA. Genotoxicity arising from triflumuron was found to be dose-dependent. Triflumuron caused a significant increase in MDA and proline levels and antioxidant enzyme activities and a significant decrease in chlorophyll a and chlorophyll b levels in direct proportion to the application concentration. In the control group, A. cepa root tip meristem cells were normal and healthy. Meristem cell damage, cortex cell damage, cortex cell wall thickening, and flattened cell nuclei were observed in A. cepa root cells treated with triflumuron insecticide. In conclusion, triflumuron is a toxic chemical to A. cepa and toxicity is both multifaceted and tends to increase with increasing doses of triflumuron.